Desain Tangga Bambu sebagai Alat Konstruksi Tradisional Berbasis Analisis Beban Statis. - Susanto, Novie; Purwaningsih, Ratna; Restuti, Dinar Anggita (Jurnal Sistem dan Manajemen Industri, 2022)
The bamboo ladder is a traditional construction equipment that still survives on the market and is in demand, especially in rural communities such as Kedalingan village. However, bamboo stairs still do not consider the standard of stairs design. In addition, there are concerns that users of the ladder may experience injury due to falls because the ladder cannot withstand the load (unbalanced). This study aims to obtain the maximum load that can be held by bamboo ladders and the angle of the position of the safe ladder by considering the Indonesian people's anthropometric weight. Calculation results based on the principle of equilibrium show that with a maximum user weight of 89.25 kg, the ladder must be positioned with a minimum slope of 53,26o but less than 65.43o. In addition, a static loading simulation was carried out using SolidWorks 2019 on a bamboo ladder frame structure that was made referring to SNI 19 - 1956 – 1990. Simulation results show that the design of a bamboo ladder can withstand a maximum body weight of 89.25 kg with the maximum load value of bamboo holding is 98.93 kg.